The role of At-Tafa’ul inspiration motivation leadership in improving organizational performance - Sulistyowati, Pemilia; Ghoniyah, Nunung; Cahyono, Budhi (Edelweiss Applied Science and Technology, 2024)
Leadership is a very important aspect because it is responsible for the sustainability of an organization. The approach method used in this study is the survey method approach. This study found a new concept, namely At-tafa’ul Inspiration Motivation Leadership (AIML) which is defined as a leadership style that is able to provide inspiration and motivation by always being optimistic in achieving the success of an organization. Optimistic leaders have a vision of a sustainable future for the company. Optimistic leaders are individuals who have stable, global and internal attributions about positive events, and unstable external attributions about adverse events. Optimism involves a realistic assessment of what can or cannot be achieved in a situation, along with a positive outcome perspective or event attribution, positive emotions, motivation and persistence. AIML has a relatively stable tendency, uses problem-focused coping strategies, reframes situations in a favorable way, and has an appropriate emotional response in dealing with problems.